Analysis of Snakebite Data from Pappinisseri Vishachikilsa Society, Kannur, Kerala (India) - Romulus Whitaker, Samir Whitaker (Calicut Medical Journal 2005;4(2):e2, 2005)
Snakebite is a significant medical issue in India, and several factors influence the region-wise incidence. This paper analyzes and reports mortality and incidence figures from one medical center in Kannur district, Kerala. The gender profile of snakebite patients showed that adult males are in the highest risk group (64 per cent of snakebite cases with envenoming), while young women and female children are in the low risk group (3.5 per cent of snakebite cases with envenoming). Snakebite seasonality was also observed in the data, the highest incidence coinciding with the start of the paddy (rice) planting season. Based on these observations, the authors have made some recommendations on the prevention and management of snakebite